Influence of resin-modified glass ionomer and topical fluoride on levels of Streptococcus mutans in saliva and biofilm adjacent to metallic brackets - Marcela Cristina Damião ANDRUCIOLI; Gisele FARIA; Paulo NELSON-FILHO; Fábio Lourenço ROMANO; Mírian Aiko Nakane MATSUMOTO
Abstract Decalcification of enamel during fixed orthodontic appliance treatment remains a problem. White spot lesions are observed in nearly 50% of patients undergoing orthodontic treatment. The use of fluoride-containing orthodontic materials has shown inconclusive results on their ability to reduce decalcification. The aims of this investigation were to compare the levels of Streptococcus mutans (SM) in saliva and biofilm adjacent to orthodontic brackets retained with a resin-modified glass ionomer cement (RMGIC) (Fuji ORTHO LC) and a light cured composite resin (Transbond XT), and to analyze the influence of topical application of the 1.23% acidulated phosphate fluoride (APF) on SM counts. In a parallel study design, two groups (n=14/15) were used with random allocation and high salivary SM counts before treatment. Biofilm was collected from areas adjacent to the brackets on teeth 13, 22, 33, and 41. Both saliva and biofilm were collected on the 7th, 21st, 35th, and 49th days after appliance placement. Topical fluoride application was carried out on the 35th day. Bonding with RMGIC did not alter SM counts in saliva or biofilm adjacent to the brackets. On the other hand, the biofilm adjacent to brackets retained with composite resin showed a significant increase in SM counts along the trial period. Topical application of 1.23% APF did not reduce salivary or biofilm SM counts regardless of the bonding material. In conclusion, fluoride topical application did not show efficacy in reducing SM. The use of RMGIC as bonding materials allowed a better control of SM cfu counts in dental biofilm hindering the significant increase of these microorganisms along the trial period, which was observed in the biofilm adjacent to the composite material.